Dynamic Performance Analysis of Radial Bogie Locomotive - LI Xiao-long; MA Wei-hua; LUO Shi-hui; LIU Wei; LV Qing-song (机车电传动)
By combination of theoretical analysis and dynamic modeling and simulation, locomotive radial bogie performance of tractionand steering and hunting stability were analyzed and compared to traditional locomotive bogie. The results showed that decreasing wheel/railattack angle was the mostly effective way to enhance curve-passing ability, and the good coordination of traction and steering was beneficialto decrease wheel/rail attack angle. However, the influence of primary longitudinal position stiffness on wheel/rail attack angle was dramaticallyin a certain range, and wheel/rail attack angle always presented larger value under traction conditions than coasting.